2009
DOI: 10.1038/aja.2009.40
|View full text |Cite
|
Sign up to set email alerts
|

Effects of DHA-enriched hen egg yolk and L-cysteine supplementation on quality of cryopreserved boar semen

Abstract: The objective of the present study was to determine the effects of docosahexaenoic acid (DHA)-enriched hen egg yolks and L-cysteine supplementation on the qualities of the cryopreserved boar semen. A total of 15 ejaculates from 5 Pietrain boars were divided into 4 groups according to the compositions of the freezing extenders used, that is, normal hen egg yolk (group I), DHA-enriched hen egg yolk (group II), normal hen egg yolk with 5 mmol L(-1) of cysteine supplementation (group III) and DHA-enriched hen egg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 58 publications
2
63
1
Order By: Relevance
“…It is observed a higher percentage of functional membrane sperm and a lower percentage of damaged cells after thawing in the diluent where 2% of salmon oil was added as compared to the control group. This result corroborates the results found by Andrade (2013) in horses and Chanapiwat et al (2009), who studied the effect of DHA semen quality of swine semen, where they found a better result obtained by the combination of egg yolk enriched in DHA + L-cysteine. This study demonstrates the importance of the role of this association in the protection of the structure and function of the plasma membrane, increasing PUFA levels in the membrane, improving its fluidity and flexibility due to the presence of some double bonds.…”
Section: Resultssupporting
confidence: 82%
“…It is observed a higher percentage of functional membrane sperm and a lower percentage of damaged cells after thawing in the diluent where 2% of salmon oil was added as compared to the control group. This result corroborates the results found by Andrade (2013) in horses and Chanapiwat et al (2009), who studied the effect of DHA semen quality of swine semen, where they found a better result obtained by the combination of egg yolk enriched in DHA + L-cysteine. This study demonstrates the importance of the role of this association in the protection of the structure and function of the plasma membrane, increasing PUFA levels in the membrane, improving its fluidity and flexibility due to the presence of some double bonds.…”
Section: Resultssupporting
confidence: 82%
“…Diluted semen was transferred to 50 mL centrifuge tubes, cooled at 15ºC for 120 min and later centrifuged at 800 × g at 15ºC for 10 min (Hettich Rotanta 460R; Andreas Hettich GmbH & Co. KG, Tuttlingen, Germany). The supernatant was discarded and the sperm pellet was re-suspended (about 1-2:1) with Extender II (80 mL of 11% lactose and 20 mL egg yolk) to a concentration of 1.5 × 10 9 spermatozoa per mL [8]. To .…”
Section: Semen Freezing Processmentioning
confidence: 99%
“…T h e i n t e g r i t y o f t h e s p e r m a c r o s o m e w a s evaluated using fluorescein isothiocyanate-labelled peanut (A. Hypogaea) agglutinin (FITC-PNA) staining [8,[24][25][26][27]. Ten µL of diluted semen with 140 µL phosphate buffered saline (PBS) was mixed with 10 µL of EthD-1 and incubated at 37ºC for 15 min.…”
Section: Assessment Of Acrosomal Integritymentioning
confidence: 99%
See 1 more Smart Citation
“…Diluted semen was transferred to 50 ml centrifuge tubes, cooled at 15°C for 120 min and later centrifuged at 800 × g 15°C for 10 min (Hettich Rotanta 460R, Andreas Hettich GmbH & Co., KG, Tuttlingen, Germany). The supernatant was discarded, and the sperm pellet was re-suspended (about 1-2:1) with extender II (80 ml of 11% lactose and 20 ml egg yolk, LEY) to a concentration of 1.5 × 10 9 spermatozoa/ml [9,23,24,29]. To prepare LEY freezing Extender II supplemented with gamma-oryzanol, two types of gamma-oryzanol-enriched rice bran oil, i.e., from a dietary supplement product (Biogrow Natural TM , Biogrow (TH) Co., Ltd., Bangkok, Thailand) and from a salad dressing and cooking oil (King TM rice bran oil, Thai Edible Oil Co., Ltd., Bangkok, Thailand) were used and prepared as follows to provide a concentration of gammaoryzanol of 0.1 mg/ml of Extender II.…”
Section: Methodsmentioning
confidence: 99%